Nutritional strategies in Covid-19 patients with gastrointestinal dysfunction - B. Ravinder Reddy (World Nutrition Journal, 2022)
Nutritional support in infections, including that due to COVID-19, is a key aspect, as it has the potential to limit the severe intensity of inflammation, to modulate optimal immune responses, whilst, limiting the loss of lean-body mass, thereby promoting enhanced recovery. However, optimal function of the gastrointestinal tract is essential to provide adequate nutrition, with optimal digestion and absorption.